Risk of waterborne virus spread – review of survival of relevant fish and crustacean viruses in the aquatic environment and implications for control measures. (19th February 2017) - Oidtmann, Birgit; Dixon, Peter; Way, Keith; Joiner, Claire; Bayley, Amanda E.
Abstract: Aquatic animal diseases are a major constraint for increasing aquaculture production. Understanding the contribution of pathogen spread from infected aquaculture sites is critical in devising control measures in the event of an outbreak. We have reviewed the available literature on the persistence in the aquatic environment of several important viral pathogens of fish and crustaceans. These include infectious haematopoietic necrosis virus, viral haemorrhagic septicaemia virus, infectious salmon anaemia virus, koi herpes virus, epizootic haematopoietic necrosis virus and infectious pancreatic necrosis virus, white spot syndrome virus (WSSV), Taura syndrome virus and yellow head virus. Some trends were common to all viruses: (i) viability declined with increasing temperature (at temperatures above 0°C); (ii) higher biological loading in water correlated with reduction in detectable viable viruses; and (iii) virus decay in water is a function of time. Most aquatic animal viruses (AAVs) remained viable for several days or weeks. WSSV is particularly stable. Comparison of studies investigating survival parameters was sometimes difficult because of the different methods employed and different ways in which the data were presented. Data gaps are identified and experimental methods employed for testing critically assessed. The information presented in this review is directly relevant to design effective control measures for AAVs and to explore measures that reduce the economic impact of disease caused by these important pathogens.